Animal-derived medicinal products in Russia: Current nomenclature and specific aspects of quality control. (10th August 2019) - Prokopov, Ilya A.; Kovaleva, Elena L.; Minaeva, Elena D.; Pryakhina, Ekaterina A.; Savin, Evgenyi V.; Gamayunova, Alexandra V.; Pozharitskaya, Olga N.; Makarov, Valery G.; Shikov, Alexander N.
Abstract: Ethnopharmacological relevance: Animal-derived medicinal products (ADMP) had been extensively used in Russia and became a part of officinal medicine in 1778. Aim of the study: The aim of the current review was to analyse the ADMPs authorised in the Russian Federation and to identify specific aspects of quality evaluation of these medicinal products. Materials and methods: Information of ADMPs was extracted from the online State Register of Medicinal Products of the Russian Federation. At the next stage, we systematically searched library catalogues, E-library.ru, Medline/PubMed, Scopus, Web of Science and Google Scholar databases to find data related to ADMP quality evaluation, clinically proven efficacy and safety. Results: For classification of ADMP, we propose an approach based on the raw material used: ADMPs derived from marine organisms, ADMPs from cattle and pigs and ADMPs from other terrestrial animals. The majority of ADMPs authorised in Russia are produced by local manufacturers. ADMPs are available in dosage forms of solution for parenteral administration (35% of all products) and lyophilisates for parenteral use (19%), tablets and capsules (17% and 11%, respectively), ointments (5%) and powders (3%). ADMPs belong to the following pharmacotherapeutic groups: medicines for tissue regeneration and repair stimulators (30%), digestive enzyme products (22%), anticoagulants (17%), proteolytic agents (6%) and medicines for the treatment of chronic prostatitis (5%). The most important approaches to standardisation of ADMPs are implementation of modern requirements for registration dossiers, development of risk-oriented approaches for evaluation of impurities, elaboration of advanced instrumental and in vitro test methods capable of replacing in vivo methods and harmonisation of the potency units used for standardisation. Conclusions: The key features of ADMPs that help them retain their leading position in the pharmaceutical market are as follows: (i) their unique composition usually represented by a complex of biologically active substances; (ii) a high degree of affinity of the active ingredient of an ADMP to the human body and (iii) proved safety and clinical efficiency. Variability in the quality of raw ingredients, epidemiological situation and other conditions pose additional challenges for the development of ADMPs and for the standardisation. Graphical abstract: Image 1